Comparison between different combinations of chemical treatment on parthenogenetic activation of mouse oocytes and its subsequent embryonic development - Abdullah, Ramli; Rahman, M.M.; Idris, S.K.; Wan Embong, W.K. (2013)
Combination of different chemicals has been an effective method to activate oocytes. The objectives of this study were to evaluate the optimal: (1) concentration (Experiment 1) and duration (Experiment 2) of strontium chloride (SrCl2) in the presence of cytochalasin B (CB), (2) secondary activation agent [6-dimethylaminopurine (6-DMAP), cycloheximide (CHX) and CB] in combination with calcium ionophore (CaI) (Experiment 3) and (3) ethanol (EtOH) concentration in combination with 6-DMAP (Experiment 4). There were no significant (P>0.05) differences in cleavage (86.82-89.06%) and blastocyst (33.42-46.83%) rates when oocytes were treated with various concentrations of SrCl2 (2-10 mM). Three-hour duration generally showed the highest cleavage (93.83%) and blastocyst rates (60.42%) compared to other durations. Comparing with various combinations, CaI +6-DMAP showed the highest cleavage at all stages of development and significantly (P<0.05) higher from other combinations at 8-cell (50.58%), morula (30.29%) and blastocyst (23.28%) stages. When comparing the EtOH concentrations, 8% EtOH gave significantly (P<0.05) highest cleavage rates at 8-cell stage (39.70%), morula (21.50%) and blastocyst (13.86%) stages followed by 9% and 7% EtOH. In conclusion, 10 mM SrCl2+5 μg/ml CB in calcium-free Chatot Ziomek Bavister medium for 3-h incubation duration gave the highest cleavage rates of parthenotes mouse oocytes. © 2013 Copyright Korean Society for Integrative Biology.